2020
DOI: 10.3390/brainsci10100739
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Gravity Treadmill Training for Freezing of Gait in Parkinson’s Disease

Abstract: Background: Parkinson’s disease (PD) is a neurodegenerative disorder characterized by motor impairment. Freezing of gait, impaired mobility and falls are common problems in these patients. We aimed to evaluate the effect of a novel therapy for these patients. Methods: We studied patients with moderate to severe freezing of gait who underwent antigravity treadmill training twice a week for 4 consecutive weeks with 50% reduction of body weight. Results: We enrolled 26 consecutive patients with PD, 19 completed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Physiotherapy is gradually emerging as therapeutic approach for FOG treatment. A recent study carried out antigravity treadmill training to improve the daily life activity ability of FOG patients (Baizabal‐Carvallo et al., 2020 ). In another examination of FOG motor networks, a novel device for deep brain electrical stimulation was used, which recorded the neural activity of the subthalamic nucleus.…”
Section: Discussionmentioning
confidence: 99%
“…Physiotherapy is gradually emerging as therapeutic approach for FOG treatment. A recent study carried out antigravity treadmill training to improve the daily life activity ability of FOG patients (Baizabal‐Carvallo et al., 2020 ). In another examination of FOG motor networks, a novel device for deep brain electrical stimulation was used, which recorded the neural activity of the subthalamic nucleus.…”
Section: Discussionmentioning
confidence: 99%
“…Physical rehabilitation is acknowledged to be crucial ( Cosentino et al, 2020 ) and there are a number of approaches that have been applied to FOG in the research setting. These include action observation training ( Pelosin et al, 2010 , 2018 ; Agosta et al, 2017 ; Mezzarobba et al, 2020 ), treadmill training ( Hong and Earhart, 2008 ; Frazzitta et al, 2009 ; Lo et al, 2010 ; Barbe et al, 2013 ; Picelli et al, 2016 ; Baizabal-Carvallo et al, 2020 ; Bekkers et al, 2020 ; Seuthe et al, 2020 ), aquatic obstacle training ( Zhu et al, 2018 ), curved walking training ( Cheng et al, 2017 ), supervised slackline training ( Santos et al, 2017 ), as well as home based exercises ( Canning et al, 2015 ). In contrast, general exercises and standard physiotherapy do not seem to be effective for the treatment of FOG ( Miller et al, 2020 ).…”
Section: Non-pharmacological Approachesmentioning
confidence: 99%
“…Antigravity treadmill was developed by the National Aeronautics and Space Administration (NASA) to train astronauts for postural and movement control in space [ 12 ]. Inside an antigravity treadmill machine, patients can walk with reduced weight load and intra-articular pressure in the lower limbs; therefore, it is an appropriate gait training approach for patients with muscle weakness [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Berthelsen et al [ 14 ] reported that early gait training using antigravity treadmill improved postural stability and gait abilities in patients with muscular dystrophy. Baizabal-Carvallo et al [ 12 ] reported that antigravity treadmill training improved gait freeze and mobility in patients with Parkinson’s disease. However, research on the effects of antigravity treadmill in stroke patients is rare.…”
Section: Introductionmentioning
confidence: 99%